The Potential of Stem Cells in the Treatment of Skeletal Muscle Injury and Disease. (19th December 2011) - MacLean, S.; Khan, W. S.; Malik, A. A.; Anand, S.; Snow, M.
Abstract : Tissue engineering is a pioneering field with huge advances in recent times. These advances are not only in the understanding of how cells can be manipulated but also in potential clinical applications. Thus, tissue engineering, when applied to skeletal muscle cells, is an area of huge prospective benefit to patients with muscle disease/damage. This could include damage to muscle from trauma and include genetic abnormalities, for example, muscular dystrophies. Much of this research thus far has been focused on satellite cells, however, mesenchymal stem cells have more recently come to the fore. In particular, results of trials and further research into their use in heart failure, stress incontinence, and muscular dystrophies are eagerly awaited. Although no doubt, stem cells will have much to offer in the future, the results of further research still limit their use.